2019
DOI: 10.1002/anie.201905635
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Interdependence of Metal–Ligand Covalency and Bond Distance Using Ligand K‐edge XAS

Abstract: Bond distance is a common structural metric used to assess changes in metal–ligand bonds, but it is not clear how sensitive changes in bond distances are with respect to changes in metal–ligand covalency. Here we report ligand K‐edge XAS studies on Ni and Pd complexes containing different phosphorus(III) ligands. Despite the large number of electronic and structural permutations, P K‐edge pre‐edge peak intensities reveal a remarkable correlation that spectroscopically quantifies the linear interdependence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…The shorter than expected bridging U−B distances suggest that the U−H−B bonds are more covalent than the Ln−H−B bonds. Consistent with this analysis, we have shown that bond length differences as small as 0.04 Å can give rise to measurable differences in metal‐ligand covalency using ligand K‐edge XAS [22] . Moreover, the 0.04 Å difference is comparable to the 0.036 Å difference reported recently by Goodwin et al.…”
Section: Methodssupporting
confidence: 91%
“…The shorter than expected bridging U−B distances suggest that the U−H−B bonds are more covalent than the Ln−H−B bonds. Consistent with this analysis, we have shown that bond length differences as small as 0.04 Å can give rise to measurable differences in metal‐ligand covalency using ligand K‐edge XAS [22] . Moreover, the 0.04 Å difference is comparable to the 0.036 Å difference reported recently by Goodwin et al.…”
Section: Methodssupporting
confidence: 91%
“…Consistent with this analysis, we have shown that bond length differences as small as 0.04 Å can give rise to measurable differences in metal-ligand covalency using ligand K-edge XAS. [22] Moreover, the 0.04 Å difference is comparable to the 0.036 Å difference reported recently by Goodwin et al for more covalent UÀ Se bonds compared to LaÀ Se in M[N-(Se=PPh 2 ) 2 ] 3 complexes. [23] Given that the bridging MÀ HÀ B bonds are the bonds that must be broken for the M 2 (H 3 BP t Bu 2 BH 3 ) 6 dimers to convert to monomers, we suspected that the thermochemical values associated with this process should reflect the enhanced covalency in the UÀ HÀ B bonds.…”
supporting
confidence: 76%
“…Spectra at the P and Cl K-edges were measured initially to probe electronic structure from the perspective of heavier atoms in the coordination sphere. Previous studies have shown that P or Cl K-edge XAS can be sensitive to bonding with phosphine or chloride ligands directly bound to metal centers. , Figure shows the background-subtracted and normalized P K-edge XAS spectra for the free ligands TRPO and their uranyl complexes UO 2 Cl 2 (TRPO) 2 . In the P K-edge XAS of the TRPO series, the pre-edge features show substantial differences with the variation of the R substituents.…”
Section: Resultsmentioning
confidence: 99%